Impacto da IFRS 3 Business combination nas demonstrações contábeis de empresas britânicas do segmento de petróleo, gás e energia, em 2005 - Borges, Railene Oliveira (2007)
The process of internationalization of the means of production and the increase of worldwide commerce of good, services and capitals strengthen the necessity of a universal, trustworthy and common language for the enterprise sector. This language is present in the accounting and financial reports. As the accounting information can change substantially from a country to another one, in accordance with the principles of accounting that govern them, and with practical the enterprise adopted, the International Accounting Standards Board - IASB - search the convergence from a National Accounting set of rules to the International Financial Reporting Standards - IFRS. This study examines the impacts proceeding from the operations of business combinations, at the financial demonstrations presented by the oil, gas and energy companies that negotiate headings in the stock market of London. The research involved a sample of 19 companies in the total of 44 organizations; those are listed in the Stock market of London (FTSE). This market was chosen by it to be member of the European Union and by this organization to compel all the companies with action in its stock markets to present its Financial Reporting in accordance with the international Standards, from 2005. But also, because the companies are part of the two main indices of evaluation of the stock market of London, the FTSE 100 and FTSE 250. As methodology, it was used documentary research and the content analysis. The study it considered the following aspects: form of fulfillments of the IFRS in 2005, use of the exceptions foreseen for the IFRS the 1 and adoption of the 3 IFRS - Business Combination. The research concluded that all the searched companies had presented the financial reporting at IFRS in 2005. All The companies presented alterations at the amount of the asset, the majority for minor. Eight companies had only evidenced impact of goodwill in the accounting reports. All the companies had informed that, in the opening balance sheet, the reevaluation of the assets for the test of Impairment was carried through, and did not have more amortization of goodwill, as determined for the IASB. The number of searched companies was small in relation to the amount of companies with actions negotiated in the Stock Exchange of London, in function of the limitation of the sector of oil, gas and energy. These considerations display limits, but they show that, for the British companies, the process of convergence of the accounting report for the International standards will go to continue.